2011
DOI: 10.1089/lap.2011.0181
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter-Resolution Fluorescence Laparoscopy of Pancreatic Cancer in a Carcinomatosis Mouse Model Visualizes Metastases Not Seen with Standard Laparoscopy

Abstract: The use of FL enables the identification of tumor foci that cannot be seen with standard laparoscopy. The technology described in this report has important potential for the clinical development of FL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In particular, the use of fluorescence-based laparoscopy for detection of pancreatic cancer has been assessed by several researchers using fluorescent-labeled proteins to aid in the surgical resection of malignant tissues. 30–33 Most of these studies found that fluorescence laparoscopy provided a simple and real-time approach for imaging to localize primary and possibly metastatic pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of fluorescence-based laparoscopy for detection of pancreatic cancer has been assessed by several researchers using fluorescent-labeled proteins to aid in the surgical resection of malignant tissues. 30–33 Most of these studies found that fluorescence laparoscopy provided a simple and real-time approach for imaging to localize primary and possibly metastatic pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies, we showed that fluorescence laparoscopy could identify tumors pre-labeled with GFP before implantation (16,17). …”
Section: Discussionmentioning
confidence: 99%
“…Toward this goal, we have recently developed a fluorescence laparoscope that permits facile and rapid identification and localization of GFP-expressing primary and metastatic tumors while maintaining adequate visualization of the surrounding tissue for proper surgical orientation and navigation (16,17). …”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic surgical systems have recently been enhanced with a fluorescence excitation light that enables imaging of fluorescently labeled tumors and metastases as well as the surrounding anatomy in orthotopic mouse models of cancer [8]. The ideal system would maximize the fluorescent intensity of tumor tissue, minimize background fluorescence, and maintain the ability for the surgeon to visualize surrounding tissues to allow for spatial orientation and surgical navigation.…”
Section: Development Of Fluorescence Laparoscopymentioning
confidence: 99%
“…With the proper filters, the sensitivity and accuracy of staging laparoscopy were significantly improved, allowing for the detection of tumor deposits that were less than 1 mm in size [8]. A second-generation fluorescence laparoscope utilized LED lighting, which was an improvement of our previously described method of fluorescence laparoscopy and allowed for enhanced tumor detection without compromising background illumination [10].…”
Section: Development Of Fluorescence Laparoscopymentioning
confidence: 99%